Protection of Mafqud Rights in Inheritance Without Court Determination According to Islamic Law - Muh. Taufik LaOde (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
The community in one of the villages in Muna Regency faces a complex inheritance dilemma, and this is not an exception. People with little legal understanding about inheritance often ignore pre-existing legal rules or conventions, such as mafqud inheritance or someone whose news is stopped, making life and death questionable. In accordance with Islamic law, a court order is required before an heir's inheritance can be distributed. The issue that exists in the community of Lakologou village is the lack of knowledge of legal requirements surrounding the role of mafqud heirs in the distribution of inheritance. According to information gathered from a number of sources, the judge's judgment will have an significant impact on the mafqud's situation in that it will subsequently offer legal certainty over whether he is still alive or otherwise. These indicators support legal actions that can be done to protect the mafqud rights, including voluntarily submitting an application to the Religious Courts as a means of protecting mafqud rights in succession.